2017
DOI: 10.1161/circresaha.116.310509
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Relevance and Role of Neuronal AT 1 Receptors in ADAM17-Mediated ACE2 Shedding in Neurogenic Hypertension

Abstract: Rationale Neurogenic hypertension is characterized by an increase in sympathetic activity and often resistance to drug treatments. We previously reported that it is also associated with a reduction of Angiotensin Converting Enzyme 2 (ACE2) and an increase in A Disintegrin And Metalloprotease 17 (ADAM17) activity in experimental hypertension. In addition, while multiple cells within the central nervous system have been involved in the development of neurogenic hypertension, the contribution of ADAM17 has not be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
172
1
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 159 publications
(183 citation statements)
references
References 53 publications
5
172
1
5
Order By: Relevance
“…ADAM17 is abundant in different organs and cleaves several cell surface enzymes, including ACE2 and NEP (8,16,23,36,38,41,54). We detected increased urinary ADAM17 in all patients with diabetes, including Dnormo.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…ADAM17 is abundant in different organs and cleaves several cell surface enzymes, including ACE2 and NEP (8,16,23,36,38,41,54). We detected increased urinary ADAM17 in all patients with diabetes, including Dnormo.…”
Section: Discussionmentioning
confidence: 69%
“…We have also reported that physical exercise training and/or metformin treatment of type 2 diabetic mice attenuated renal ADAM17 expression and shedding of urinary ACE2 (44). Recently, it was demonstrated that Ang II type 1 receptors promote ADAM17 mediated ACE2 shedding in hypertensive patients (54). In addition, in vitro studies showed that the release of ACE2 into the culture media of human proximal tubular cells was inhibited by treatment with the ADAM17 inhibitor TNF-␣ protease inhibitor-1 (41).…”
Section: Introductionmentioning
confidence: 87%
“…In primary cultures of neurons and glial cells isolated from brainstem and hypothalamus of 1-day-old rats, nicotine treatment resulted in increased expression of AT 1 R but decreased expression of ACE2, and these nicotine effects were greater in cells isolated from spontaneously hypertensive rats compared with Wistar-Kyoto rats (43,44). The above findings provide strong evidence that interaction between nicotine and the brain RAS may contribute to the sympatho-mimetic actions of nicotine as well as AT 1 R-mediated neurogenic hypertension (144).…”
Section: Nicotine and The Ras In The Nervous Systemmentioning
confidence: 66%
“…ACE2 is a known substrate of ADAM17 (534). The importance of neuronal AT 1 Rs in mediating upregulation of ADAM17 and downregulation of ACE2 in humans and in DOCA-salt hypertension highlights the importance of neuronal AT 1 R clinically and in experimental hypertension (1168,1177).…”
Section: Sympathoexcitatory Actionmentioning
confidence: 99%